Central Bank Financial Strength, Transparency, and Policy Credibility - Stella, Peter (IMF Working Papers; Working Paper ;, 2002)
A central bank is financially strong if it possesses resources sufficient to attain its fundamental policy objective(s). Once endowed with those resources, relations between government and central bank should be designed so that significant changes in central bank financial strength do not occur unless necessitated by changes in policy objectives. The level of strength required depends on the array of policy objectives (for example, the exchange rate regime) as well as the constraints and risks presented by the operational environment. Attaining credibility is facilitated if the public can easily determine the financial strength of the bank, yet for a variety of reasons this is often difficult. Transparency requires institutional arrangements that ensure the central bank generates profit in most states of the world, is subject to strict ex post independent audit, and transfers regularly all profits, after provisions, to the treasury.